Valid and Practical Powtoon-Based Learning Media for Science Learning: Media Pembelajaran Berbasis Powtoon yang Valid dan Praktis untuk Pembelajaran Sains - Sullaisah, Fajriahsari; Nurlina; Rahmawati (Indonesian Journal of Innovation Studies, 2025)
General Background: Science learning outcomes in Indonesian elementary schools remain suboptimal, often due to monotonous instruction and limited engaging media. Specific Background: The Kurikulum Merdeka emphasizes interactive and technology-integrated learning, yet teachers frequently rely on textbooks and traditional methods, which reduce students’ motivation and conceptual understanding. Knowledge Gap: Previous studies explored general animation-based media, but the integration of Powtoon for contextualizing abstract science concepts in Grade V, particularly on Earth Changes, remains underexplored. Aims: This study aimed to develop Powtoon-based learning media and evaluate its validity, practicality, and effectiveness in improving science learning outcomes. Results: Using the DDD-E model with 28 fifth-grade students, findings revealed the media was rated very valid by experts, highly practical by teachers and students, and significantly effective, with posttest scores surpassing pretest results (N-gain = 0.8, high category). Novelty: Unlike prior research, this study uniquely integrates Powtoon into the Kurikulum Merdeka context, providing a systematic design aligned with learning objectives while addressing cognitive achievement gaps. Implications: Powtoon-based media can serve as an innovative alternative to enrich digital pedagogy, enhance student motivation and comprehension, and support teachers in creating creative, engaging, and curriculum-aligned science instruction.Highlight : Powtoon media development improves science learning outcomes. Validity, practicality, and effectiveness are proven. Student engagement and understanding significantly increase. Keywords : Learning Media Development, Powtoon, Science, Learning Outcomes, DDD-E